Estimation of Soil-Water Characteristic Curve for Cohesive Soils with Methylene Blue Value - Junhui Zhang; Junhui Peng; Yejuan Chen; Jue Li; Feng Li (Advances in Civil Engineering)
This study described a new methylene blue test to measure the methylene blue value (MBV) for 15 cohesive soils and established the relationship between MBV and plasticity index (PI) and between MBV and percent passing No. 200 sieve (P200), respectively. Thereafter, the soil-water characteristic curves (SWCCs) for 15 cohesive soils based on Fredlund and Xing’s model were generated by the pressure plate test. Then, regression equations for determining the four fitting parameters in a previously developed SWCC equation by using the measured MBV were utilized to generate the SWCC for the cohesive soils. At the same time, the slope parameter, bf, in the SWCC equations was found to be associated with the moisture susceptibility of cohesive soils. A higher bf value indicates that the material is more moisture susceptible. In addition, a lower MBV/PI/P200 shows a lower suction at the same degree of saturation; on the other hand, a higher MBV/PI/P200 presents a higher suction. Therefore, the moisture-holding capacity of cohesive soils increases with increasing MBV, PI, and P200. Finally, the proposed estimation method was validated by a comparison between the four determined fitting parameters from MBV and the pressure plate test.